MAXIMIZATION OF GROWTH AND YIELD OF CAYENNE PEPPER WITH TEA LEAF DREGS COMPOST - achmad fatchul aziez; Daryanti; wiyono; R. Sulistijono; Sapto Priyadi; Solikhun (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2022)
Fertilization is needed by plants, including cayenne pepper. Organic fertilizers have advantages because of the complete composition of nutrients. Tea leaf dregs which is an organic fertilizer that contains a number of nutrients that are quite good for cayenne pepper plants. This study aims to determine the effect of tea leaf dregs compost on the growth and yield of cayenne pepper. The research was carried out in Beji village, East Ungaran, Semarang district from February to June 2017 with latosol soil type. The design used was a single factor completely randomized design with 18 replications. The levels were without tea leaf dregs compost, doses of tea leaf dregs compost were 10, 20, 30, and 40 tons/ha. The results showed that the most productive branches were at a dose of tea leaf dregs compost of 20 tons/ha, dry weight of stover 40 tons/ha, fruit weight per plant 30 tons/ha, and flowering age 20 tons/ha and harvest age 30 tons/ha. The conclusion of this study was that tea leaf dregs compost increased the number of productive branches, dry weight of stover and fruit weight per plant, and accelerated flowering and harvesting ages. The implication of this research is that the cultivation of cayenne pepper should use tea leaf dregs compost at a dose of 30 tons/ha.